2011
DOI: 10.1097/icl.0b013e3182188a77
|View full text |Cite
|
Sign up to set email alerts
|

Do Scores on a Tachistoscope Test Correlate With Baseball Batting Averages?

Abstract: Tachistoscopic test scores correlated positively with batting averages. The tachistoscope may be an acceptable tool to help in assessing batting performance. Additional testing with players from different sports, different levels of ability, and different tachistoscopic times should be performed to determine if the tachistoscope is a valid measure of athletic ability. Implications may also be drawn in other areas such as military and police work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…In addition, performance on the Perception Span task exhibits some association with both higher walk rates and increased slugging percentages, though the evidence is not conclusive. This task measures the ability to remember and recreate visual patterns and may reflect visual recognition abilities that have previously been tied to batting performance in small samples of players (N = 20) tested with Tachistoscopic methods 7 and in a conference paper reporting relationships in collegiate players 8 . For reference, across the tested models we find expected age and position effects with stronger batting performance for outfields and older batters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, performance on the Perception Span task exhibits some association with both higher walk rates and increased slugging percentages, though the evidence is not conclusive. This task measures the ability to remember and recreate visual patterns and may reflect visual recognition abilities that have previously been tied to batting performance in small samples of players (N = 20) tested with Tachistoscopic methods 7 and in a conference paper reporting relationships in collegiate players 8 . For reference, across the tested models we find expected age and position effects with stronger batting performance for outfields and older batters.…”
Section: Discussionmentioning
confidence: 99%
“…However, the combination of noisy game statistics and costly sample acquisition makes inferring meaningful relationships difficult. Although a small number of studies have reported links between superior baseball statistical production and better visual reaction times 4 , dynamic stereoacuity 5 , binocular divergence 6 , and visual recognition 7 , 8 , they are based on small sample sizes and/or appear in conference proceedings, rather than peer reviewed articles.…”
Section: Introductionmentioning
confidence: 99%
“…The eyes account for 80% of the information taken into the brain. Having good vision and training that vision to be proficient may provide the batter with a competitive edge [6] , [8] . It is estimated that the average visual acuity of a professional baseball player is 20/12 whereas college players are of the order of 20/15 [6] .…”
Section: Discussionmentioning
confidence: 99%
“…The Tachistoscope is a device that trains the brain to recognize images faster, and loosely correlates to batting average [8] . We flash numbers on a screen, typically starting with 1 number at 0.25 seconds, gradually adding more numbers [up to 4] randomly placed on the screen, and also including different backgrounds at increasingly faster flashes.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, there are multiple instances of concurrent technologies having significant correlations, and by extension acceptable reliability, while exhibiting numerical differences in absolute magnitude that impede its validity (O'Donnell et al, 2018). In addition, there is also a specific history in the world of baseball player development in using technology that may be highly reliable while measuring outcomes on different scales of magnitude, like the tachistoscope test correlating with a player's batting average (Reichow et a., 2011).…”
Section: Discussionmentioning
confidence: 99%